Documenting and defining emergent phenomenology: theoretical foundations for an extensive research strategy - Sandilands, Olivier; Ingram, Daniel M. (Frontiers in Psychology, 2024)
Meditation, psychedelics, and other similar practices or induction methods that can modulate conscious experience, are becoming increasingly popular in clinical and non-clinical settings. The phenomenology associated with such practices or modalities is vast. Many similar effects and experiences are also reported to occur spontaneously. We argue that this experiential range is still not fully described or understood in the contemporary literature, and that there is an ethical mandate to research it more extensively, starting with comprehensive documentation and definition. We review 50 recent clinical or scientific publications to assess the range of phenomena, experiences, effects, after-effects, and impacts associated with a broad variety of psychoactive compounds, meditative practices, and other modalities or events. This results in a large inventory synthesizing the reports of over 30,000 individual subjects. We then critically discuss various terms and concepts that have been used in recent literature to designate all or parts of the range this inventory covers. We make the case that specialized terminologies are needed to ground the nascent research field that is forming around this experiential domain. As a step in this direction, we propose the notion of "emergence" and some of its derivatives, such as "emergent phenomenology", as possibly foundational candidates.